Determinanti della formazione di imprese nei servizi alla produzione in Italia - Roberta Piergiovanni; Enrico Santarelli (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1993)
– This paper deals with the determinants of new furn formation in the business servicesin Italy during the second half of the 19805. For this purpose we use the data base made recentlyavailable by the National Instimte of Social Security, which provides information on both newly andalready established firms with at least one employee. Two birth rates are computed and analysed forthe 95 Italian provinces: the first one is an index of fertility represented by the share of newenterprises on employees, the second one is a typical birth rate represented for each province by theratio between new enterprises and resident population. Looking at the determinants of this process, we found that the average wage rates affect negatively the index of fertility, and that the potentialdemand for new business services affects positively the birth rate. The index of fertility is alsoexplained by a dummy variable which identifies for each province those policies which are aimed atfostering the process of new furn formation. The birth rate is instead affected by a dummy variablewhich is equal to one for the provinces where are located the chief towns of each region (which areassumed to "attract" the most innovative among the new Gums) and zero otherwise. Finally, bothindexes are affected positively by the sector growth and by an index of small flrm presence andnegatively by the ratio of utilized credit to the total line of credit.
Keywords: 330